Xenon (New Jersey) Commercial Burglary Data, 1979-1981 - Gibbs, John J. ([Verlag nicht ermittelbar], 1984)
This data collection is one of three quantitative databases comprising the Commercial Theft Studies component of the Study of the Causes of Crime for Gain, which focuses on patterns of commercial theft and characteristics of commercial thieves. This data collection contains information on commercial burglary incidents in Xenon, New Jersey. The data collection includes incident characteristics, theft item, value of stolen property, and demographic information about the suspect(s), such as police contacts, number of arrests, sex, race, and age.